2010
DOI: 10.1186/1471-2164-11-437
|View full text |Cite
|
Sign up to set email alerts
|

Comparative microarray analysis of Rhipicephalus (Boophilus) microplus expression profiles of larvae pre-attachment and feeding adult female stages on Bos indicus and Bos taurus cattle

Abstract: BackgroundRhipicephalus (Boophilus) microplus is an obligate blood feeder which is host specific to cattle. Existing knowledge pertaining to the host or host breed effects on tick transcript expression profiles during the tick - host interaction is poor.ResultsGlobal analysis of gene expression changes in whole R. microplus ticks during larval, pre-attachment and early adult stages feeding on Bos indicus and Bos taurus cattle were compared using gene expression microarray analysis. Among the 13,601 R. microplu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 100 publications
1
32
0
Order By: Relevance
“…The primary line of host defense also relies on complex hemostatic and immunological responses of the host against ectoparasites. For example, ticks counteract the host response and successfully survive attached to the skin of their host via the secretion of a complex mixture of molecules present in tick saliva (Rodriguez-Valle et al, 2010;Chmelar, 2016;Xu et al, 2016). Host -parasite interactions have been studied using proteomic and transcriptomic analyses of economically important ticks such as A. americanus (Aljamali et al, 2009), D. andersoni (Alarcon-Chaidez, 2007, Ixodes pacificus (Francischetti et al, 2005), Rhipicephalus microplus (Rodriguez- Valle et al, 2010), and others.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The primary line of host defense also relies on complex hemostatic and immunological responses of the host against ectoparasites. For example, ticks counteract the host response and successfully survive attached to the skin of their host via the secretion of a complex mixture of molecules present in tick saliva (Rodriguez-Valle et al, 2010;Chmelar, 2016;Xu et al, 2016). Host -parasite interactions have been studied using proteomic and transcriptomic analyses of economically important ticks such as A. americanus (Aljamali et al, 2009), D. andersoni (Alarcon-Chaidez, 2007, Ixodes pacificus (Francischetti et al, 2005), Rhipicephalus microplus (Rodriguez- Valle et al, 2010), and others.…”
Section: Discussionmentioning
confidence: 99%
“…For example, ticks counteract the host response and successfully survive attached to the skin of their host via the secretion of a complex mixture of molecules present in tick saliva (Rodriguez-Valle et al, 2010;Chmelar, 2016;Xu et al, 2016). Host -parasite interactions have been studied using proteomic and transcriptomic analyses of economically important ticks such as A. americanus (Aljamali et al, 2009), D. andersoni (Alarcon-Chaidez, 2007, Ixodes pacificus (Francischetti et al, 2005), Rhipicephalus microplus (Rodriguez- Valle et al, 2010), and others. These reports concluded that tick proteins secreted into the tick's attachment site inhibit host hemostatic and immunological responses by diverse mechanisms (Francischetti et al, 2009) sequences which leads to important structural modifications that affect their specific functions (Schwarz et al, 2014;Chmelar, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Novel high-throughput sequencing techniques allow generation of qualitative and quantitative information on unknown transcriptomes, in addition to gene array-based analysis. This has been successfully used to study transcriptional changes induced by blood-feeding in tick larvae (Rodriguez-Valle et al 2010). It will be interesting to analyze whether arbovirus infection of ticks and tick cells leads to differential regulation of numerous pathways and genes as seen in mosquitoes and which of them in particular, in addition to RNAi, mediate antiviral activity.…”
Section: Control Of Arbovirus Infection By Vector Innate Immune Respomentioning
confidence: 99%